1962
DOI: 10.1002/bit.260040404
|View full text |Cite
|
Sign up to set email alerts
|

Mean light intensity—a useful concept in correlating growth rates of dense cultures of microalgae

Abstract: SummaryAn analysis of the distribution of light within some culture vessels developed at. General Dynamics/Electric Boat is presented. The concept of a mean effective light intensity, E, is introduced and procedures are developed for computing i ?for any culture vessel geometry and incident light intensity distribution. A correlation is performed indicating the significance of E in assessing the growth rate of dense, continuous cultures of microalagae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

1964
1964
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 5 publications
2
28
0
1
Order By: Relevance
“…It should be noted that the APFD and APAR models showed the relatively poor prediction, although these models have been popularly used (Aiba, 1982;Iehana, 1983Iehana, , 1990Koizumi and Aiba, 1980;Molina Grima et al, 1994, 1997Prokop and Erickson, 1995;Rabe and Benoit, 1962;Van Liere and Mur, 1979). Previous studies on the APFD or APAR model did not use experimental results obtained over broad ranges of incident light intensity and cell density.…”
Section: Performance Of Modelsmentioning
confidence: 89%
See 3 more Smart Citations
“…It should be noted that the APFD and APAR models showed the relatively poor prediction, although these models have been popularly used (Aiba, 1982;Iehana, 1983Iehana, , 1990Koizumi and Aiba, 1980;Molina Grima et al, 1994, 1997Prokop and Erickson, 1995;Rabe and Benoit, 1962;Van Liere and Mur, 1979). Previous studies on the APFD or APAR model did not use experimental results obtained over broad ranges of incident light intensity and cell density.…”
Section: Performance Of Modelsmentioning
confidence: 89%
“…Symbols used in this work are summarized in Table I. Rabe and Benoit (1962) suggested that the average photon flux density could be correlated with the specific growth rate. This implies that the average photon flux density could be a representative value of spatially distributed density within the photobioreactor.…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these values are valid only at low cell concentrations and a narrow light path, and give no information on local light energy distribution inside the culture. Thus, bioengineers have developed mathematical models to obtain the light distribution profile and average light intensity (Cornet et al, 1992;Lee et al, 1987;Molina Grima et al, 1997;Rabe and Benoit, 1962). Since the average light intensity can be identical for completely different conditions, the light distribution profile is required to describe the irradiance conditions more precisely.…”
Section: Introductionmentioning
confidence: 99%